The Role of Local Supply Chains in Supporting Sustainable Tourism Development - Shahparan, Mohammad (PT. Riset Press International, 2025)
Sustainable tourism is the most important part of preserving natural and cultural resources. Sustainable tourism development also helps to promote long-term economic benefits. One of the most important elements of sustainable tourism is the involvement of the local supply chain which not only allows for sustainable tourism development but also contributes to the local communities. This qualitative research explores the role of the local supply chain in supporting sustainable tourism development. This study also highlights community participation, encouraging business practice, provide a unique experience for tourists with sustainable concepts. Monitoring and evaluating the role of local supply chains can help refine the rules and improve the results. By implementing a local supply chain government can create a sustainable and equitable tourism sector.